Blended Formula Four Di (4D) with Actor Network Theory to Increases the Outcome of Literacy Culture - Tri Wahyu Liswati (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2020)
The purpose of this research is to evaluate the effectiveness of the Blended Formula Four Di (4D) with Actor Network Theory in increasing the outcome of literacy culture is a case study that involves all school members. The obtained data were analysed by using qualitative descriptive methods. The analysis results inform that the Blended Formula Four Di (4D) with Actor Network Theory has proven to be effective in improving the outcome of literacy culture in schools. The application of